IN VITRO FERMENTABILITY, DEGRADABILITY AND MICROBIAL BIOMASS PRODUCT OF COMPLETE RATION CONTAINING A COMBINATION OF FIELD GRASS, CONCENTRATE AND NUTRIENT RICH SUPPLEMENT - Wahyuni, D.S.; Tjakradidjaja, A.S.; Suharyono, S. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
The objective of this experiment was to obtain an optimum combination between field grass,concentrate and Nutrient Rich Supplement (NRS) based on in vitro study using Hohenheim gas test. Theexperimental diets were: R1 (control diet = 70% field grass + 30% concentrate), R2 (70% field grass +25% concentrate + 5% NRS), R3 (70% field grass + 20% concentrate + 10% NRS) and R4 (70% fieldgrass + 15% concentrate + 15% NRS). A randomized block design with four treatments and fourreplications was carried out. Buffalo rumen fluid was taken in different time and was used as block orreplication. Data were analyzed by Analysis of Variance (ANOVA). Significant differences amongtreatments were determined by contrast orthogonal. The results showed that total gas production andtotal VFA concentration were highest (P<0.05) in R4 among the treatments. Addition of 15% NRS incomplete ration (R4) increased NH3 concentration 10.34%. Addition of 10% NRS and 15% NRS incomplete ration (R3 and R4) improved the microbial biomass product compared to control and 5% NRSin complete ration (R1 and R2). Dry matter (DM) and organic matter (OM) degradability weresignificantly higher (P<0.01) in 10% NRS and 5% NRS in complete ration (R3 and R2) compared tocontrol and 15% NRS in complete ration (R1 and R4). It was concluded that combination between 70%field grass, 20% concentrate and 10% NRS in complete ration (R3) was more optimal for improving gasproduction, total VFA, NH3 concentration, microbial biomass product, dry matter degradability andorganic matter degradability, compared to control ration.